There Is Still No Silver Bullet. - Grier, David Alan (Computer (00189162), 2021)
Throughout its existence, Computer has been at the center of discussion over how software should be engineered and how it should be developed. No article has been so central to the discussion as "No Silver Bullet" by Frederick P. Brooks. Yet, almost 35 years after he wrote this contribution to knowledge, Brooks's observation remains true. Software engineering is a complex and demanding field that poses a host of problems to the practitioner, and there is no single solution, that is, no silver bullet, that will provide a simple way to reduce the work required to create a software product.